biometric identification of capilariid eggs from archaeological sites in Patagonia - Taglioretti, Verónica (2014)
Numerous eggs of capillariid nematodes have been found in coprolites from a wide range of hosts and in raptor pellets in archaeological samples from Patagonia. The structure and sculpture of the eggshell of these nematodes and their biometry are commonly used for identification. The aim of this study was to determine whether eggs of the genus Calodium with similar morphology, found in different archaeological samples from Patagonia, belong to the same species. For this purpose, capillariid eggs (N ¼ 843) with thick walls and radial striations were studied by permutational multivariate analysis of variance (PERMANOVA). Eggs exhibiting similar shape and structure also showed similar biometry, regardless of the zoological origin of coprolites (P ¼ 0.84), host diet (P ¼ 0.19), character of the archaeological sites (P ¼ 0.67) and chronology (P ¼ 0.66). Thus, they were attributed to the same species. We suggest that an unidentified zoonotic species of the genus Calodium occurred in the digestive tract of a wide range of hosts in Patagonia during the Holocene and that both human and animal populations were exposed to this parasite during the Holocene in the study area.